2018
DOI: 10.1111/cas.13732
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant methylation and silencing of the SPINT2 gene in high‐grade gliomas

Abstract: Hepatocyte growth factor activator inhibitor type 2 (HAI‐2), encoded by the SPINT2 gene, is a membrane‐anchored protein that inhibits proteases involved in the activation of hepatocyte growth factor (HGF), a ligand of MET receptor. Epigenetic silencing of the SPINT2 gene has been reported in a human glioblastoma cell line (U87) and glioblastoma‐derived cancer stem cells. However, the incidence of SPINT2 methylation in tumor tissues obtained from glioma patients is unknown. In this study, we analyzed the methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
(87 reference statements)
0
8
0
Order By: Relevance
“…Regarding dysregulation of the HGF/MET signaling pathway, the SPINT2 gene has been extensively studied in gliomas. It encodes hepatocyte growth factor activator inhibitor type 2 (HAI-2), which is a membrane-anchored protein and a serine proteinase inhibitor that hinders proteases involved in the activation of HGF [48]. In human gliomas, HAI-2 expression levels are inversely correlated with histological grade, and reduced expression was found to be associated with progression [49].…”
Section: Hai-2 and The Hgf/met Signaling Pathway In Gliomamentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding dysregulation of the HGF/MET signaling pathway, the SPINT2 gene has been extensively studied in gliomas. It encodes hepatocyte growth factor activator inhibitor type 2 (HAI-2), which is a membrane-anchored protein and a serine proteinase inhibitor that hinders proteases involved in the activation of HGF [48]. In human gliomas, HAI-2 expression levels are inversely correlated with histological grade, and reduced expression was found to be associated with progression [49].…”
Section: Hai-2 and The Hgf/met Signaling Pathway In Gliomamentioning
confidence: 99%
“…In human gliomas, HAI-2 expression levels are inversely correlated with histological grade, and reduced expression was found to be associated with progression [49]. Moreover, in high-grade glioma, higher SPINT2 expression was determined to be associated with better OS [48]. Basic experimental research also showed that MET phosphorylation levels and glioblastoma tumor growth are reduced by the expression of HAI-2 both in vitro and in intracranial xenografts in nude mice, and that HAI-2 suppresses fibrinolytic activities and inhibits the Matrigel invasion of glioblastoma cell lines [48, 49].…”
Section: Hai-2 and The Hgf/met Signaling Pathway In Gliomamentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, HAI-2/SPINT2 may not be a physiological inhibitor of serum HGFAC. On the other hand, HAI-2/SPINT2 may function as an HGFAC inhibitor to suppress HGF-MET signaling in cancer tissues [ 44 ]. Further studies are required to define the roles of HAI-2/SPINT2 in HGF-MET signaling in vivo.…”
Section: Regulation Of Hgfac Activity By Endogenous Proteinase Inhmentioning
confidence: 99%
“…Lee and colleagues [31] examined SPINT2 promoter hypermethylation in GBMs and GSC lines and observed associated reductions in SPINT2 mRNA expression in GSC lines; they similarly demonstrated reduced cell growth and migration following forced SPINT2 expression in U87 cells. A study published as this manuscript was being prepared also identified hypermethylation of the SPINT2 gene in human glioma-derived cell lines and high-grade glioma tissue samples [38].…”
Section: Discussionmentioning
confidence: 94%